PENGARUH STUDI AL-QUR’AN TERHADAP PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN DARUSSALAM KOTO ANAU SOLOK - Deddy Irawan; Muhammad Taufiq (CV. Adiba Aisha Amira, 2025)
The increasing phenomenon of moral deviance in students seen in the millennial era is really worrying for the world of education, so one of the efforts to shape the religious character of students is through the tahfidz al-Qur'an program. This research aims to determine the implementation of the tahfidz Al-Qur'an program and the formation of the religious character of students. An important aspect of this research is the implementation of the tahfidz Al-Qur'an program and the formation of religious character which includes: Methods, stages, indicators as well as supporting and inhibiting factors for the formation of the tahfidz Al-Qur'an program internally and externally at the Darussalam Koto Anau Islamic Boarding School. This research uses a qualitative approach. The data collection methods used are observation, interviews and documentation methods. The research results show (1) The implementation of the tahfidz Al-Qur'an program is good and running smoothly; (2) The formation of the religious character of students is said to be good by applying methods of example, habituation, advice and methods of reward and punishment. The stages are the stages of knowledge, awareness, practice, habituation and maintaining religious character values. Indicators for the formation of religious character include: akhlakul karimah, polite speech, congregational prayers, dhuha prayers, praying before and after learning, saying greetings when meeting, morning imtaq activities and reading yasin and ratib on Friday nights. Internal supporting factors: health, intelligence and motivation. External factors: cooperation of all parties, competent tahfidz teachers, time management, government response, internal inhibiting factors: laziness, impatience, despair, difficulty managing time and often forgetting. External factors: economic capabilities and material density.